Fast Speed Control of AC Machines Without the Proportional-Integral Controller: Using an Extended High-Gain State Observer - Wang, Fengxiang; Wang, Junxiao; Kennel, Ralph M.; Rodriguez, Jose (IEEE transactions on power electronics, 2019)
As cascaded proportional-integral controllers involve complicated tuning work, many efforts have been focused on direct controllers. Direct torque control and predictive torque control are both feasible solutions. However, bigger ripples or weighting factor designs are not easily solved. In this paper, a direct current controller that uses an extended high-gain state observer is proposed. The integral controller is removed from the system by using a disturbance estimation technique, which improves the system's performance with a variety of loads. A direct current controller without weighting factors is proposed as the inner controller. Unlike existing direct control methods, all phase currents are considered equally in the controller, which ensures a high current control quality. The simulation and experimental results verify that the proposed method performs well both in steady and transient states.